1996
DOI: 10.1021/bi960482k
|View full text |Cite
|
Sign up to set email alerts
|

Motion of Spin-Labeled Side Chains in T4 Lysozyme. Correlation with Protein Structure and Dynamics

Abstract: Thirty single cysteine substitution mutants of T4 lysozyme have been prepared and spin-labeled with a sulfhydryl-specific nitroxide reagent in order to systematically investigate the relationship between nitroxide side-chain mobility and protein structure. The perturbation caused by replacement of a native residue with a nitroxide amino acid was assessed from the resulting changes in biological activity, circular dichroism, and free energy of folding. The nitroxide produced context-dependent changes in stabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

70
951
0
4

Year Published

1997
1997
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 587 publications
(1,025 citation statements)
references
References 47 publications
70
951
0
4
Order By: Relevance
“…The secondary structure and hydrophilicity patterns should be sufficient for introduction of spin labels with a high level of success. EPR studies have shown that the nitroxide spin label MTSL is readily introduced into all secondary structure elements (particularly helices) and in general does not significantly perturb protein structure (22).…”
Section: Resultsmentioning
confidence: 99%
“…The secondary structure and hydrophilicity patterns should be sufficient for introduction of spin labels with a high level of success. EPR studies have shown that the nitroxide spin label MTSL is readily introduced into all secondary structure elements (particularly helices) and in general does not significantly perturb protein structure (22).…”
Section: Resultsmentioning
confidence: 99%
“…The line shapes of EPR spectra reflect the dynamic modes of the nitroxide side chain that can be modulated by protein backbone fluctuation, tertiary interaction, etc [24,[30][31][32]. Each EPR spectrum along the sequence provides site-specific dynamic information.…”
Section: Resultsmentioning
confidence: 99%
“…The electron paramagnetic resonance (EPR) spectrum of a spin label side chain encodes information regarding the rate and amplitude of label motion, which in turn is dictated by the local structure and tertiary contact made by the spin label side chain. 11 Local protein backbone fluctuations also modulate the motion of spin-labeled side chains, making EPR spectra sensitive to backbone dynamics on the ns timescale 12,13 ; moreover, conformational transitions that result in altered local structure or tertiary contact are easily detected by EPR, as are distinct conformational substates that are in equilibrium.…”
Section: Introductionmentioning
confidence: 99%